Theology and the public: reflections on Hans W. Frei on hermeneutics, Christology, and theological methods - Shin, Daniel D. (Lexington Books, 2019)
Theological hermeneutics -- Frei's early hermeneutics: realistic narrative interpretation -- Realistic narrative and the public -- Frei's later hermeneutics: the literal reading -- Christology -- The unsubstitutable identity of Jesus -- The church and the world -- Theological method -- Theology and the academy -- Use of philosophy in Christian theology -- Theology and historical-critical inquiry